2021
DOI: 10.3390/ijerph18147445
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress among Students in Higher Education: One Year after the Beginning of the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has affected the psychological well-being of students. Several stressors (such as socioeconomic and education-related contexts) could influence mental health, as well as individual and relational dimensions. This study proposes to evaluate the predictive effect of these factors on anxiety and depressive symptoms among students in higher education one year after the beginning of the pandemic. A sample of 23,307 students (Mage = 20.89; SD = 1.96; 69.08% of women) was assessed through an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 43 publications
5
25
0
Order By: Relevance
“…At the time of the present survey, university lockdown for preventing Covid-19 viral infections had sustained for about a year and a half. At this stage, NBGs reported more loneliness, fewer contacts with family members and, in line with other studies (Prout et al, 2020;de Graaf et al, 2021;Schmits et al, 2021) more psychic stress symptoms, than BGs did, and their FUNCT was poorer than that of BGs although effects of other factors were controlled.…”
Section: Covid-19 Effects Of Functioning and Gendersupporting
confidence: 87%
See 2 more Smart Citations
“…At the time of the present survey, university lockdown for preventing Covid-19 viral infections had sustained for about a year and a half. At this stage, NBGs reported more loneliness, fewer contacts with family members and, in line with other studies (Prout et al, 2020;de Graaf et al, 2021;Schmits et al, 2021) more psychic stress symptoms, than BGs did, and their FUNCT was poorer than that of BGs although effects of other factors were controlled.…”
Section: Covid-19 Effects Of Functioning and Gendersupporting
confidence: 87%
“…However, detrimental effects of Covid-19 do not distribute evenly in the society. In population surveys young age, female and non-binary gender, working outside home, living with children and low resilience and assets have associated with psychological distress experiences, like depression, anxiety and post-traumatic stress symptoms (Gómez-Salgado et al, 2020;Prout et al, 2020;Guldager et al, 2021;Hou et al, 2021aHou et al, , 2021bSchmits et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These restrictive confinement measures put in place to counter the virus’ spread could have major consequences for mental health. Indeed, several studies conducted in China and in Europe have reported high levels of depressive and anxiety symptoms as well as poor sleep quality, and younger people have reported a significantly higher prevalence of generalized anxiety disorder and depression [ 7 , 9 , 10 , 11 , 12 , 13 , 14 ]. Furthermore, the restrictive measures are likely to increase the risk of family violence and reduce the options for support [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Belgium, a study assessed psychiatric symptoms among higher education students one year after the pandemic. They found that 50.6% of students presented anxiety symptoms, 55.1% had depressive symptoms, 20.8% had suicidal thoughts, 42.4% felt their financial situation had deteriorated, and 39.1% had dropping out thoughts ( Schmits et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%